Ecofeminismo e o ensino de biologia : sexismo e especismo nas falas de estudantes veganas - Oliveira, Valéria Santos Santana (2020)
Starting from historical considerations that show the most compatible Science with abilities stimulated in male gender, we emphasize here the importance of debating themes that approximate the teaching of Biology to the feminine. Firstly, we reflect on approximations between the teaching of Biology and the ecofeminist movements, that denounce the systems of patriarchal oppression. In second place, we seek to understand if indicators of a compatible consciousness with the ecofeminist construction can be harvested of the speeches of vegan women about how they have built their relations of affection with animals to the point of no longer feeding on them. Lastly, we search to understand if starting from these reports we can construct reflections about a teaching of Biology more compatible with the affectivity and the feminine. Summarizing, this research aim to analyze indicators of ecofeminist elements in the speeches of vegan women over how they have built a relation of affection with the nature and not human animals, with especial attention to the themes of sexism and speciesism and how this relation may contribute to the Biology teaching. For this, was applied eight semi-structured interviews with vegan students of the Federal University of Sergipe (FUS). This quantity was defined by speech saturation criteria. The reports were recorded, transcribed and interpreted from the Thematic Content Analysis proposed by Bardin. The depositions showed affective approaches of the students’ stories with the nature and the animals. In contrast, still according to the reports, the teaching of Biology that taught in classroom still needs a progress over the empathy with not human animals and the nature in a general way. Also was possible to identify an intrinsic relation between the sexism and speciesism, by means of gender prejudice that exists in society. This factor that presents the human being as superior in relation to others animals, that in turn are separated, in those that can be consumed and those which can be seen as part of the family. Betimes is possible that we can build a teaching of Biology more feminine, seeking to understand what women teach in their fights.